Electronics simplified - Sinclair, Ian Robertson (Elsevier, 2011)
Electronics Simplified is essential reading for everyone who wants to know more about the electronics revolution. No previous knowledge is assumed, and by focusing on how systems work, rather than on details of circuit diagrams and calculations, this book introduces you to the key principles and technology of modern electronics without needing access to expensive equipment or laboratories. This approach also enables you to gain a firm grasp of the principles they will be applying in the lab. Explains electronics from fundamentals to applications - No other book has such breadth of coverage Approachable, clear writing style, with minimal math - No previous knowledge of electronics required! Now fully revised and updated to include coverage of the latest developments in electronics: Blu-ray, HD, 3-D TV, digital TV and radio, miniature computers, robotic systems and more.